SUCCESSFUL MANAGEMENT OF EGG - BOUND SYNDROME IN A NON-DESCRIPT HEN BY MILKING METHOD - N.R. Bhathra,; Chhavi Gupta,; V. Prabaharan,; A. Sabarinathan,; A. Ganesan, (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 38-week-old non-descript laying hen weighing 2.1 kg was presented with the complaint of anorexia and failure to lay eggs for the past 4 days. Clinical examination revealed that the bird had frequent cloacal straining and further egg-like hard mass was palpable on digital examination. Radiographic examination confirmed egg-bound syndrome. The vent was cleaned and cloacal mucosa was desensitized. By gentle digital milking two intact eggs and a broken egg were retrieved. Post-operatively the hen was administrated with Inj. Oxytocin @ 1IU i/m along with antibiotic therapy for 7 consecutive days.